PRAGMATIC FEATURES OF REPROACH IN SPOKEN AND WRITTEN DISCOURSE - Mukhtorova, Mokhlaroyim (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study investigates the pragmatic features of reproach in both spoken and written discourse. Reproach, defined as a speech act conveying disapproval or criticism, is a key component in interpersonal communication and is used to manage social relationships. Using a combination of qualitative and quantitative methods, the research analyzes how reproach is realized in spoken and written forms, exploring the differences in strategies and their functions. Drawing on data from both natural conversations and written texts, the study examines the contextual factors that influence the pragmatics of reproach. The findings reveal that while the core strategies of reproach are similar across modalities, their realization and social impact differ significantly between spoken and written forms. These differences are attributed to factors such as immediacy, tone, and the ability to modulate the force of the reproach.